2021
DOI: 10.1002/jnr.24978
|View full text |Cite
|
Sign up to set email alerts
|

Faim knockout leads to gliosis and late‐onset neurodegeneration of photoreceptors in the mouse retina

Abstract: Fas Apoptotic Inhibitory Molecule protein (FAIM) is a death receptor antagonist and an apoptosis regulator. It encodes two isoforms, namely FAIM-S (short) and FAIM-L (long), both with significant neuronal functions. FAIM-S, which is ubiquitously expressed, is involved in neurite outgrowth. In contrast, FAIM-L is expressed only in neurons and it protects them from cell death. Interestingly, FAIM-L is downregulated in patients and mouse models of Alzheimer's disease before the onset of neurodegeneration, and Fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…The obese phenotype described by Lam’s group was not reproduced in a second Faim -KO mice generated by Dr. Rothstein’s group ( Kaku and Rothstein, 2020 ), and in our study with the former model some phenotypic characteristics changed based on the genetic background of the mice strain used. However, our group recently identified a retinal neurodegenerative phenotype in Dr. Huo’s model, compatible with the observations on protein homeostasis reported by Dr. Rothstein ( Sirés et al, 2021 ). Several factors can influence the appearance of phenotypes when analyzing mice models, such as genetic background of mice strain, flanking genes modifications during the generation of the mice, KO generation methodology, or environmental factors.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The obese phenotype described by Lam’s group was not reproduced in a second Faim -KO mice generated by Dr. Rothstein’s group ( Kaku and Rothstein, 2020 ), and in our study with the former model some phenotypic characteristics changed based on the genetic background of the mice strain used. However, our group recently identified a retinal neurodegenerative phenotype in Dr. Huo’s model, compatible with the observations on protein homeostasis reported by Dr. Rothstein ( Sirés et al, 2021 ). Several factors can influence the appearance of phenotypes when analyzing mice models, such as genetic background of mice strain, flanking genes modifications during the generation of the mice, KO generation methodology, or environmental factors.…”
Section: Introductionsupporting
confidence: 88%
“…Therefore, FAIM-L decrease in AD could also be pathologically linked to a more rapid, aggressive Aβ aggregation. In a Faim-KO mice model ( Huo et al, 2016 ), we identified the presence of ubiquitinated aggregates throughout the retina, a gliotic activation response in the Müller cells, and pronounced vascular leakage that lead to late-onset photoreceptor cell death ( Sirés et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, the effects of FAIM on c-FLIP expression are not fully understood. FAIM has been reported to exert its biological effects by reducing ubiquitination; FAIM was found to reduce the ubiquitination and degradation of XIAP via direct interaction [ 48 ], FAIM knockout led to the presentation of ubiquitinated aggregates in the retina [ 49 ], and FAIM protects glutaminase C from ubiquitination and induces cancer cell proliferation in lung adenocarcinoma [ 14 ]. Here, we found that FAIM could maintain c-FLIP stabilization under hypoxic conditions by protecting c-FLIP from ubiquitination and degradation, thus protecting MSCs from apoptosis.…”
Section: Discussionmentioning
confidence: 99%